The Tradition of Khatam Qur’an at the Grave of the Padang Bolak Community - Ilham Ramadan Siregar; Syaripah Aini; Akhyar Akhyar (UIN Sumatera Utara Medan, 2022)
This study aims to describe the culture of khatam Qur’an at the grave that are preserved by the Padang Bolak people. The study was conducted using an ethnographic approach by directly observing and participating in khatam activities. The results of this study analyze the background of the growth of the khatam tradition in relation to the entry of Islam into the Padang Bolak area, the doctrine of tariqat/suluk being the most important in this section. The khatam process at the grave is usually carried out based on the parents' will for those left behind or at the initiation of the family who feels responsible. Although it is not considered fardhu kifayah, khatam Qur’an at the grave is voluntary in nature as well as a standard of value for the community in the form of devotion to parents. Another conspicuous concern in the procession lies in the accommodation and service which erodes the financial loss of the who got calamity.